The Employer Approach to Industrial Relations Research - Boyd, J. (Relations industrielles / Industrial Relations, 1966)
In his article, the author shall emphazise that the managers role is to relate technology to human values. Traditionally, the governing value has been productivity in the economic sense. He shall suggest that a wider range of human values must be supported, e.g. the satisfying growth of the individual employee.